The effects of Fe2O3 nanoparticles on catalytic function of human acetylcholinesterase: size and concentration role - Samaneh Rashtbari; Zahra Hassanpour Aydinlou; Leila Sadeghi (BioImpacts)
Introduction: Fe2O3 NPs can enter cells quickly, pass through the blood-brain barrier and interact with macromolecules. These materials are widely used in different fields, so their risk assessment is among the most critical issues. Acetylcholinesterase (AChE) is a cholinergic enzyme in central and peripheral nervous systems. Methods: In this work, the possible effects of Fe2O3 NPs on the structure and catalytic activity of AChE were investigated using circular dichroism (CD), surface plasmon resonance (SPR), and fluorescence spectroscopies. Results: The outcomes demonstrated that 5 nm Fe2O3 NPs inhibit AChE activity through mixed mechanism. While 50 nm Fe2O3 NPs caused an enhancement in the catalytic activity up to 60 nM. However, higher concentrations of Fe2O3 NPs (above 60 nM) hindered the enzyme activity via mixed mechanism. Fluorescence analysis showed that NPs can quench the fluorescence intensity of AChE that refer to conformational changes. Furthermore, CD results showed that Fe2O3 NPs can reduce the α-helix and β-sheet contents of the enzyme and decrease the stability of AChE. Also, the SPR data analysis showed that the affinity between AChE and Fe2O3 NPs decreased with rising temperature. After treatment with Fe2O3 NPs, the catalytic activity of AChE was assessed in HepG2 cell lines, and the results confirmed the inhibitory effects of Fe2O3 NPs on AChE activity in vivo. Conclusion: These findings provide helpful information about the impact of Fe2O3 NPs on the structure and function of AChE and could offer new insights into the risk assessment of the medical application of nanoparticles.